Construção e calibração de lisímetros de barras de pesagem e evaporação da água do solo em função de resíduos culturais de soja e trigo - Mariano, Daiane de Cinque (2013)
Crop residues affects soil evaporation by changing energy balance and flux of water vapor on the soil surface. Weighing lysimeters enable the measurement of evaporation to quantify the effects arising from crop residues in cultivation system such as the no-tillage system. In the standard lysimeters, the weighing system generally includes a load cell attached to a weighing scale with levers of mass decrease. The high cost of the mechanical parts in the weighing scale, combined with wide offer of low cost electronics for data collection, makes viable to build weighing bar lysimeters with four load cells in each device. This study aimed to: construct and calibrate four new lysimeters built of rectangular double tanks of approximately 1.35 m² of surface and 1.50 m of depth, supported by two weighing bars and to use weighting lysimeters to analyze the effect of the quantity and distribution of soil surface crop residues on the soil water evaporation. Each lysimeter had two weighing barssupported by two loading cells of high accuracy, connected to a junction box by a coaxial cable and then to a datalogger. Calibration of each lysimeters was performed after field installation. The results showed linear response (R2> 0.9999) of electric signal (mV) to mass increase or decrease (kg), with minimum hysteresis. Mean absolute error of mass estimate (0.0245 a 0.2844 equivalent-mm) and Wilmott index between observed and estimated data (d = 1.0000) indicate a high precision of the new equipment. The results allow concluding that the lysimeters constructed are appropriate for estimation of evapotranspiration and on components of soil water balance. Soil water evaporation as a function of mulching (0, 2, 4 and 6 t ha-1) and also as function of 4 t ha-1 of soybean mulching applied to cover 33, 66, 100% was measured in two drying cycles for each trial, eight weighting lysimeters in Londrina, PR. For two experiments soybean residue was used duringFall/Winter wheat residue was used we usedduring spring/summer. At the beginning of each drying period, irrigation of 50 mm was applied. The cumulative evaporation curves at the end of each period of drying set the second degree polynomial, with significant decreases in the quantity (0.99 ≥ R2 ≥ 0.86) and mulching distribution (0.99 ≥ R2 ≥ 0.74). Significant decreases were observed of the evaporation during the autumn with the increase of quantity of applied residue, contrasting the treatments 4 and 6 t ha-1, with 28 and 43%, respectively. Evaporation as a function of the quantity of crop residue follow a second degree polynomial. Soil water evaporation decreased with increase of rate of soybean residue, distribution evenly about the lysimeter during of period of Autumn/Winter. Stood out in two cycles evaluated treatments 100%, with evaporation rates of 33 and 29%, compared to bare soil. The quantity and distribution crop residues decreases the evaporation and furthers a higher retention of water in the soil, what makes it available to the plants for a longer period of time.